Tasks of Technical Operation and Maintenance of Passenger Transport of Automobile Enterprises (Texas Journal of Engineering and Technology, 2022)
The need for rolling stock is established based on the need to assign to each route such anumber of buses of a certain passenger capacity, which provides a minimum of the carrier's costs,provided that the passenger traffic is mastered in compliance with regulatory requirements for the qualityof transport services